Novel non-canonical role of STAT1 in Natural Killer cell cytotoxicity. (1st September 2016) - Putz, Eva Maria; Majoros, Andrea; Gotthardt, Dagmar; Prchal-Murphy, Michaela; Zebedin-Brandl, Eva Maria; Fux, Daniela Alexandra; Schlattl, Andreas; Schreiber, Robert D.; Carotta, Sebastian; Müller, Mathias; Gerner, Christopher; Decker, Thomas; et al.
ABSTRACT: STAT1 is an important regulator of NK cell maturation and cytotoxicity. Although the consequences of Stat1 -deficiency have been described in detail the underlying molecular functions of STAT1 in NK cells are only partially understood. Here, we describe a novel non-canonical role of STAT1 that was unmasked in NK cells expressing a Stat1-Y701F mutant. This mutation prevents JAK-dependent phosphorylation, subsequent nuclear translocation and cytokine-induced transcriptional activity as verified by RNA-seq analysis. As expected Stat1-Y701F mice displayed impaired NK cell maturation comparable to Stat1 −/− animals. In contrast Stat1-Y701F NK cells exerted a significantly enhanced cytotoxicity in vitro and in vivo compared to Stat1 −/− NK cells in the absence of detectable transcriptional activity. We thus investigated the STAT1 interactome using primary NK cells derived from Stat1 ind mice that inducibly express a FLAG-tagged STAT1. Mass spectrometry revealed that STAT1 directly binds proteins involved in cell junction formation and proteins associated to membrane or membrane-bound vesicles. In line, immunofluorescence studies uncovered the recruitment of STAT1 to the target-cell interphase during NK cell killing. This led us to propose a novel function for STAT1 at the immunological synapse in NK cells regulating tumor surveillance and cytotoxicity.